2016
DOI: 10.1111/emed.12154
|View full text |Cite
|
Sign up to set email alerts
|

Bands of brothers: a re‐appraisal of the Viking Great Army and its implications for the Scandinavian colonization of England

Abstract: Although the ninth‐century Viking Great Army has been subject to intensive historical and archaeological study, it remains an enigmatic entity. This article explores the evidence for the Great Army in England through the consideration of archaeological materials in addition to the organizational structures underpinning the formation of Viking ‘armies’. In light of this, I argue that the Great Army is better considered as a mobile society or polity rather than an armed force. Viewing the Great Army in this way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…This would face the challenge of distinguishing contributions of Danish Vikings from those of earlier migrants to Britain from the near Continent in the early middle Ages [ 28 ]. Additionally, the picture within the Danelaw is complicated by historical factors such as the composition of the Viking Great armies, which were much less homogenous in origin than previously believed [ 45 ], as well as by potential large-scale movements, such as the influx of Dublin Vikings in 902 CE. Archaeological investigations have shown diversity of origin within groups buried in the same place [ 46 ], which indicates high levels of mobility within the Danelaw.…”
Section: Discussionmentioning
confidence: 99%
“…This would face the challenge of distinguishing contributions of Danish Vikings from those of earlier migrants to Britain from the near Continent in the early middle Ages [ 28 ]. Additionally, the picture within the Danelaw is complicated by historical factors such as the composition of the Viking Great armies, which were much less homogenous in origin than previously believed [ 45 ], as well as by potential large-scale movements, such as the influx of Dublin Vikings in 902 CE. Archaeological investigations have shown diversity of origin within groups buried in the same place [ 46 ], which indicates high levels of mobility within the Danelaw.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than being a study in which Viking-Age archaeology and later textual sources are compared with anthropological data, we are instead, as in our 2017 paper, employing evolutionary theory and ethnographic evidence to generate predictions, which we then test with the material and literary records. As other aspects of our research have shown (Raffield andothers 2016, 2017), the incorporation of evolutionary concepts into the study of the Viking Age can shed light on contemporaneous social attitudes and practices that are otherwise difficult to explore through traditional methods of archaeological and historical enquiry. Importantly, our 'prediction testing' approach does not involve forcing the archaeological and literary evidence to fit a pattern.…”
Section: List Of Illustrationsmentioning
confidence: 69%
“…101–105). Recent work has examined the make‐up of vikings armies and their building blocks of warrior bands (Raffield, 2016; Raffield, Greenlow, Price, & Collard, 2016, p. 37). Viking activity to the east, leading to the creation of Rus' through interactions with other groups, has generally been seen as trading and settlement more than raiding and therefore as less violent.…”
Section: Modern Trends: Ideology Heritage Warrior Mentalitymentioning
confidence: 99%